Quality elements of rice processing; rice millers view on quality during rice production - Zulpikri, Muhammad Afif; Nasirun, Noraini; Mohamed Kassim, Kamsol; Muhammad Noor, Sarina (2017)
Purpose - Rice is one of the important crops in the world. It is also one of the daily foods for more than half of total humanity in this world or two-third of the world population (Singha, 2013). In Malaysia, rice is the staple food which is consumed daily food for almost all of the Malaysian.The study shows that every Malaysian consumed two and half plates of rice per day (Rajamoorthy et al., 2015). There are a few types of rice produced in the Malaysian market based on the quality specifications set by BERNAS, the first one is Super Tempatan 15% (ST15) which contains 85% of head rice and 15% of broken rice. The second one is, Super Tempatan 10% which contains 90% of head rice and 10% of broken rice and lastly is Super Tempatan 5% which contain of 95% of head rice and another 5% of broken rice (Chung, Arshad, Noh, & Sidique, 2016).PadiBeras Nasional Berhad or BERNAS is given the right to import and distribute rice until 2021 (Rittgers & Wahab, 2017).One of its responsibilities is to ensure that the paddy industry in Malaysia does not face any problem related to consumption of rice. Thus, BERNAS must promote market stability and maintain a stabilized rice price so that it is affordable by the consumer.In addition, BERNAS is also responsible to ensure the supply of rice is sufficient and accessible for all citizens in Malaysia (Muhammad, 2013).Hence, as spelled out in The Review of Paddy and Rice Industry in Malaysia (2004), the main objective of BERNAS is to ensure food security for paddy and rice industry, raise the income and productivity of the paddy farmers and to make sure that the food supply to consumers is fair and the price is stable.